The discovery of Scaphyglottis punctulata (Laeliinae) in the highlands of Brazilian Amazonia with a key to the species of the region - de Araújo, Adriane Maciel; Farroñay, Francisco; Perdiz, Ricardo de Oliveira; Pessoa, Edlley; Giacomin, Leandro (Lankesteriana: International Journal on Orchidology, 2022)
The genus Scaphyglottis Poepp. & Endl. presents 78 species and occurs from Mexico to Brazil. Scaphyglottis punctulata (Rchb.f.) C.Schweinf. is known from various high elevation locations from Panama to Bolivia. Here, we report new records in two regions of the Brazil portion of the Guiana Shield. We provide a detailed description, photographic plates, updated distribution map, ecological and taxonomic comments for S. punctulata, and an identification key for Scaphyglottis species from the Brazilian portion of the Guiana Shield.